Educational transmedia narratives and the INAEP method: innovation and learning in the Colombian Context. Pilot study - García-Rojas, Maribel; Mañas-Olmo, Moisés; Aranda, Lourdes; Cortés-González, Pablo (Frontiers in Education, 2024)
This pilot study examined how higher education students in Colombia perceived innovation while interacting with a transmedia product. The study aimed to determine the perceived innovation in students as prosumers of a transmedia product called “El Bogotazo” and to evaluate the impact of the INAEP method on their learning. A quantitative correlational methodology was employed, involving 57 students from fields such as Advertising, Marketing, Business Administration, Accounting, and Law. A 20-question Likert-type survey assessed dimensions like innovation perception, learning, prosumer behavior, and ICC. Preliminary results showed significant direct relationships among all dimensions. Notably, students’ perceived innovation strongly correlated with their learning and prosumer roles in educational transmedia narratives. The study highlighted the importance of CCIs in education, positioning students as active prosumers and revealing the relationship between CCIs, innovation, and learning. The discussion confirmed the INAEP method’s potential to measure 21st-century competencies, emphasizing innovation, educational transmedia narratives, and students’ active roles in learning.